Recombinant bromelain production in Escherichia coli: process optimization in shake flask culture by response surface methodology - Muntari, Bala; Amid, Azura; Jami, Mohammed Saedi; Mohd. Salleh, Hamzah; Mel, Maizirwan (Springer, 2012)
Bromelain, a cysteine protease with various therapeutic and industrial applications, was expressed in Escherichia coli, BL21-AI clone, under different cultivation conditions (post-induction temperature, L-arabinose concentration and post-induction period). The optimized conditions by response surface methodology using face centered central composite design were 0.2% (w/v) L-arabinose, 8 hr and 25°C. The analysis of variance coupled with larger value of R2 (0.989) showed that the quadratic model used for the prediction was highly significant (p < 0.05). Under the optimized conditions, the model produced bromelain activity of 9.2 U/mg while validation experiments gave bromelain activity of 9.6 ± 0.02 U/mg at 0.15% (w/v) L-arabinose, 8 hr and 27°C. This study had innovatively developed cultivation conditions for better production of recombinant bromelain in shake flask culture.